Planning and Development of Land Bill. - Government of the Republic Trinidad and Tobago. (Government of the Republic Trinidad and Tobago., 2011)
An Act relating to the planning and development of land.
www.ttparliament.org/publications.php?mid=28andid=484
Keywords: Development planning Laws - Trinidad and Tobago, Urban planning, Land development – Legislation, Physical planning - Environmental management, Regional planning, Planning and Development of Land Act